Lithium aluminum silicon glass-ceramic, preparation method and production system
By using composite crystal nucleating agents and rare earth dopants, the transformation of quartz solid solution in lithium-aluminum-silicon microcrystalline glass is suppressed, and the problems of transparency, expansion coefficient and transmittance are solved, and the effects of lower expansion coefficient and high transmittance are achieved, while improving mechanical strength.
Patent Information
- Application Number
- CN202410046816.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-01-12
AI Technical Summary
During the crystallization process of lithium-aluminum silicon-based microcrystalline glass, the quartz solid solution is easily converted into spodumene, affecting its transparency, expansion coefficient and transmittance.
Titanium oxide, zirconium oxide, phosphorus pentoxide and lithium fluoride are used to form a composite crystal nucleant, combined with cerium dioxide and neodymium trioxide as rare earth dopants, and through specific heat treatment procedures and production system design, the transformation of quartz solid solution to spodumene is inhibited.
A transparent lithium aluminum-silicon-based microcrystalline glass with a lower expansion coefficient and a high transmittance was obtained, and its mechanical strength was improved.
Smart Images

Figure CN118047539B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of glass, and specifically relates to a lithium aluminum silicon glass-ceramic, a preparation method and a production system. Background Art
[0002] Glass-ceramics is a polycrystalline material made by adding nucleating agents and other raw materials to ordinary glass. The material is first melted to form ordinary glass, and then subjected to a certain heat treatment to precipitate crystals and combine with residual glass. It has the advantages of extremely low expansion coefficient (theoretically zero expansion), high mechanical strength, high flexural and compressive strength, and heat resistance. It is an ideal material for electronic materials, functional materials, and building materials.
[0003] At present, the production of crystallized glass products requires two basic heat treatment processes: annealing (removing internal stress) and crystallization (changing the crystal phase), which are completed by two devices, namely the annealing furnace and the crystallization furnace. This type of equipment is basically improved from the original ceramic plate tunnel kiln. The equipment is mainly brick-structured, and the heating element is an electric heating wire sheathed outside the ceramic tube, which is heated up and down by the radiation of the electric heating wire.
[0004] Because the heating tubes are arranged parallel to the upper and lower directions of the conveying rollers, there is a large temperature difference between the two sides and the middle of the furnace, which has a great impact on the crystallization of the microcrystalline glass and makes the quality of the product uncontrollable. Especially when producing lithium aluminum silicon transparent microcrystalline glass, as the grains grow, the quartz solid solution can easily transform into spodumene, thereby affecting the transparency, expansion coefficient and transmittance of the lithium aluminum silicon microcrystalline glass. Summary of the invention
[0005] In view of the fact that the quartz solid solution of the above-mentioned existing lithium aluminum silicate glass is easily transformed into spodumene during crystallization, thereby affecting the transparency, expansion coefficient and transmittance of the lithium aluminum silicate glass-ceramics; one of the purposes of the present application is to provide a lithium aluminum silicate glass-ceramics, a preparation method and a production system, which can inhibit the transformation of the quartz solid solution into spodumene, thereby producing transparent lithium aluminum silicate glass-ceramics with a lower expansion coefficient and high transmittance.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] The present application discloses a production system of microcrystalline glass, which has a batching device, a melting furnace, a calendering device and a crystallization annealing furnace; wherein the crystallization annealing furnace includes a roller kiln, and a primary annealing zone, a nucleation zone, a crystallization zone and a secondary annealing zone are sequentially arranged along the feeding and discharging directions; a mesh belt conveyor, wherein the mesh belt is laid on the roller of the roller kiln and moves along the feeding and discharging directions under the action of the roller; a heating component is arranged in the heating sections of the primary annealing zone, the nucleation zone, the crystallization zone and the secondary annealing zone, and is located at the upper and lower sides of the roller; a radiation member is arranged between the heating component and the roller to separate the heating component and the roller.
[0008] Preferably, the heating assembly includes a first heating element, which is symmetrically arranged on the upper and lower sides of the roller and is horizontally equidistantly arranged along the feeding and discharging directions, and both ends of the first heating element are fixed on the kiln walls on both sides of the roller kiln; a second heating element is located on both sides of the roller kiln and extends vertically along the kiln top of the roller kiln to the interior of the roller kiln.
[0009] A lithium aluminum silicon series microcrystalline glass, the raw materials of which include a main material, a crystal nucleus agent, a clarifier and a rare earth dopant.
[0010] The components of the crystal nucleating agent and their mass fractions of the total weight of the raw materials include: titanium oxide (TiO2) 0.5% to 1.0%; zirconium oxide (ZrO2) 1.5% to 2.3%; lithium fluoride (LiF) (P2O5) 1.0% to 2.5% and phosphorus pentoxide (P2O5) 1.0% to 2.5%. The components of the rare earth dopant and their mass fractions of the total weight of the raw materials include neodymium trioxide (Nd2O3) 0.01% to 0.05%; cerium dioxide (CeO2) 0.05% to 0.13%.
[0011] Preferably, the mass fraction of the clarifier to the total weight of the raw materials is 0.8% to 1.2%; the clarifier is composed of sodium nitrate (NaNO3), ammonium chloride (NH4Cl), arsenic trioxide (As2O3) and antimony trioxide (Sb2O3).
[0012] Preferably, in the present application, the components of the clarifier include, by mass fraction of the weight of the clarifier: 10% to 25% sodium nitrate (NaNO3); 10% to 20% ammonium chloride (NH4Cl); and 60% to 80% of a mixture of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3).
[0013] Preferably, the main crystalline phase of the lithium aluminum silicon glass-ceramics is a quartz solid solution.
[0014] Preferably, the components of the main material and their mass fractions of the total weight of the raw materials include: silicon dioxide (SiO2) 68% to 73%; lithium oxide (Li2O) 3.1% to 4%; aluminum oxide (Al2O3) 13% to 18%; magnesium oxide (MgO) 0.7% to 1.2%; zinc oxide (ZnO) 0.8% to 1.4%; calcium oxide (CaO) 0.4% to 0.7%; boron oxide (B2O3) 0% to 0.2%; and a mixture of potassium oxide (K2O) and sodium oxide (Na2O) 1.8% to 2.1%.
[0015] The present application also discloses a method for preparing lithium aluminum silicon glass-ceramics, comprising the following steps:
[0016] S1. Proportioning: mixing and grinding the main material and the crystal nucleating agent as described in the above scheme, and mixing with the clarifier and the rare earth dopant to obtain a uniform mixture;
[0017] S2, melting and clarification: placing the mixed material in a melting furnace, melting it at 1600°C to 1650°C, and then clarification treatment to obtain glass liquid;
[0018] S3, cooling and molding;
[0019] S4, stress relief annealing: anneal the formed glass at 600℃~650℃ for 1h~2h;
[0020] S5, nucleation: heating the annealed glass to 700°C to 750°C for nucleation treatment for 0.5h to 2h;
[0021] S6, crystallization: the nucleated glass is further heated to 850°C to 900°C for crystallization treatment for 1h to 2h;
[0022] S7. Cool to obtain lithium aluminum silicon glass-ceramics.
[0023] Preferably, in step S5, the temperature is increased to 700°C to 750°C at a heating rate of 8°C / min to 10°C / min.
[0024] Preferably, in step S6, the temperature is increased to 850°C to 900°C at 4°C / min to 6°C / min.
[0025] Preferably, in step S7, the temperature is first lowered to 500°C to 550°C at a rate of 15°C / min to 20°C / min, kept at that temperature for 0.5h to 1h, and then air-cooled to room temperature.
[0026] From the above description, it can be seen that the beneficial effects of this application are:
[0027] 1. Since the present application adopts titanium oxide (TiO2), zirconium oxide (ZrO2), phosphorus pentoxide (P2O5) and lithium fluoride (LiF) to form a composite nucleus agent, the "synergistic effect" of the nucleus agent can be used to form a large number of nuclei in the glass and inhibit the growth of the nuclei. At the same time, cerium dioxide (CeO2) and neodymium trioxide (Nd2O3) reduce the viscosity of the glass and promote crystallization, and are combined with the rapid heating system of the preparation method to control the growth of grains, obtain fine and uniformly distributed grains, inhibit the transformation of quartz solid solution to spodumene, and then obtain transparent lithium aluminum silicon microcrystalline glass with low expansion coefficient and high transmittance. On the other hand, cerium dioxide (CeO2) and neodymium trioxide (Nd2O3) are also beneficial to improving the mechanical strength of microcrystalline glass.
[0028] 2. By introducing sodium nitrate (NaNO3) and ammonium chloride (NH4Cl) on the basis of traditional clarifiers arsenic trioxide (As2O3) and antimony trioxide (Sb2O3), the volatile pollution of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3) can be effectively avoided, and the usage of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3) can be reduced.
[0029] 3. The crystallization annealing kiln heats both sides of the roller kiln through the second heating element to supplement the heat dissipated outward from both sides of the roller kiln, thereby reducing the horizontal temperature difference in the kiln; at the same time, by setting the radiation element, the first heating element and the second heating element first heat the radiation element, and then the radiation element heats the glass on the mesh belt, which is beneficial to improve the temperature uniformity and avoid the quality of the microcrystalline glass being affected by uneven temperature during heat treatment of the glass; and by transporting through the mesh belt conveyor, the phenomenon of broken plates can be avoided, which is beneficial to improve the qualified rate of microcrystalline glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or related technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is a schematic diagram of the longitudinal section structure of the crystallization annealing furnace of the production system of the present application.
[0032] Figure 2 This is a schematic diagram of the cross-sectional structure of the crystallization annealing furnace of the production system of the present application.
[0033] Figure numerals: 10 - roller kiln; 11 - roller; 20 - mesh belt; 31 - first heating element; 32 - second heating element; 40 - radiation element. DETAILED DESCRIPTION
[0034] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0035] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in the specification of this application are only for describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0037] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0038] The embodiments of the present application are described in detail below.
[0039] The embodiment of the present application discloses a lithium aluminum silicon series glass-ceramics, the raw materials of which include a main material, a crystal nucleating agent, a clarifier and a rare earth dopant.
[0040] Among them, the main material contains the following components and their mass fractions of the total weight of the raw materials are:
[0041] Silicon dioxide (SiO2) 68%~73%, lithium oxide (Li2O) 3.1%~4%, aluminum oxide (Al2O3) 13%~18%, magnesium oxide (MgO) 0.7%~1.2%, zinc oxide (ZnO) 0.8%~1.4%, calcium oxide (CaO) 0.4%~0.7%, boron oxide (B2O3) 0%~0.2%, a mixture of potassium oxide (K2O) and sodium oxide (Na2O) 1.8%~2.1%.
[0042] The nucleating agent contains the following components and their mass fractions in the total weight of the raw materials are: titanium oxide (TiO2) 0.5% to 1.0%, zirconium oxide (ZrO2) 1.5% to 2.3%, lithium fluoride (LiF) 1.0% to 2.5%, and phosphorus pentoxide (P2O5) 1.0% to 2.5%.
[0043] In the present embodiment, titanium oxide (TiO2), zirconium oxide (ZrO2), phosphorus pentoxide (P2O5) and lithium fluoride (LiF) are used to form a composite nucleus agent. 5+ ) tetrahedral coordination and phosphate network formation ability, induce glass phase separation, and promote the nucleation process of glass; at the same time, phosphorus pentoxide (P2O5) can increase the solubility of zirconium oxide (ZrO2), improve the melting of glass and the nucleation of zirconium oxide (ZrO2); on the other hand, lithium fluoride (LiF) can significantly reduce the crystallization temperature and crystallization dynamics of glass; by utilizing the "synergistic effect" of the crystal nucleating agent, the glass can form a large number of crystal nuclei and inhibit the growth of crystal nuclei, which is conducive to obtaining fine and uniformly distributed grains, thereby improving the mechanical properties of lithium aluminum silicon microcrystalline glass. In practical applications, the amount of titanium oxide (TiO2) can be appropriately reduced and the amount of zirconium oxide (ZrO2) can be increased to improve the flexural strength of the glass.
[0044] The mass fraction of the clarifier to the total weight of the raw materials is 0.8% to 1.2%, and it is composed of sodium nitrate (NaNO3), ammonium chloride (NH4Cl), arsenic trioxide (As2O3) and antimony trioxide (Sb2O3).
[0045] More specifically, the mass fractions of the components of the clarifier are: sodium nitrate (NaNO3) 10% to 25%, ammonium chloride (NH4Cl) 10% to 20%, and a mixture of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3) 60% to 80%.
[0046] In the embodiment of the present application, sodium nitrate (NaNO3) and ammonium chloride (NH4Cl) are introduced on the basis of the traditional clarifiers arsenic trioxide (As2O3) and antimony trioxide (Sb2O3); sodium nitrate (NaNO3) and ammonium chloride (NH4Cl) are both decomposed at about 350°C to generate oxygen (O2) and hydrogen chloride (HCl), respectively; wherein hydrogen chloride (HCl) activates arsenic trioxide (As2O3) and antimony trioxide (Sb2O3), which can promote the clarification of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3). The oxidation degree of antimony (Sb2O3) is such that arsenic trioxide (As2O3) and antimony trioxide (Sb2O3) are oxidized into arsenic pentoxide (As2O5) and antimony pentoxide (Sb2O5), which can effectively avoid the volatile pollution of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3) and reduce the usage of arsenic trioxide (As2O3) and antimony trioxide (Sb2O3); at the same time, hydrogen chloride (HCl) can also promote the dissolution of raw materials and rare earth dopants, and chloride ions (Cl - ) can reduce the surface tension of the glass liquid during clarification, thus helping to improve the clarification effect.
[0047] The rare earth dopant contains the following components and their mass fractions in the total weight of the raw materials: neodymium oxide (Nd2O3) 0.01% to 0.05%, cerium dioxide (CeO2) 0.05% to 0.13%.
[0048] In the embodiment of the present application, rare earth-doped lithium aluminum silicon glass-ceramics are obtained by adding rare earth elements cerium (Ce) and neodymium (Nd) to the raw material components. Cerium (Ce) and neodymium (Nd) can reduce the viscosity of the glass, promote crystallization, and inhibit the transformation of the quartz solid solution to spodumene, which is beneficial to improving the mechanical properties of the glass. At the same time, by co-doping with cerium (Ce) and neodymium (Nd), the coloring of the glass by the inevitable iron (Fe) element impurities in the glass production process is avoided, which is beneficial to improving the transmittance of the glass.
[0049] It should be noted that in actual production, it is necessary to avoid adding too much cerium dioxide (CeO2), otherwise the glass will be colored, thus affecting the transmittance of the glass.
[0050] The beneficial effects of the present application are further described below by means of specific embodiments.
[0051] Example 1, Table 1 shows the formula composition of the lithium aluminum silicon system glass-ceramics of the present application, and the lithium aluminum silicon system glass-ceramics No. 1 to 12 shown in Table 1 are prepared using the following method:
[0052] (1) Weigh the components of the main material and the crystal nucleating agent according to the ratio requirements recorded in Table 1, grind the components evenly, and mix them with the clarifier and rare earth dopant to prepare a mixed material.
[0053] (2) The mixed material is heated to 1600°C to 1650°C to melt, and then clarified to obtain molten glass.
[0054] (3) Cooling and molding.
[0055] (4) Annealing the formed glass at 600°C to 650°C for 1 h to 2 h to obtain basic lithium aluminum silicon glass.
[0056] (5) The base lithium aluminum silicate glass is heated to 700°C to 750°C at a heating rate of 8°C / min to 10°C / min and subjected to a nucleation treatment for 0.5h to 2h.
[0057] (6) Then, the temperature is increased to 850°C to 900°C at a heating rate of 4°C / min to 6°C / min and the crystallization treatment is performed for 1 h to 2 h.
[0058] (7) Then cool to 500°C to 550°C at a rate of 15°C / min to 20°C / min, keep warm for 0.5h to 1h, and then air-cool to room temperature for secondary annealing; thus, lithium aluminum silicon glass-ceramics whose main crystalline phase is quartz solid solution is obtained.
[0059] The performance and appearance of the lithium aluminum silicon glass-ceramics with test numbers 1 to 12 are shown in Table 2.
[0060] By comparison, the flexural strength, thermal shock resistance, transmittance and expansion coefficient of No. 1 to 7 and No. 9 to 12 are significantly better than No. 8, that is, by doping with rare earth dopants, transparent lithium aluminum silicon glass-ceramics with lower expansion coefficient, high transmittance and better thermal shock resistance can be produced.
[0061] Example 2, using the composition recorded in No. 4 in Table 1 as raw materials to prepare glass-ceramics, comprising the following steps:
[0062] (1), (2), (3), and (4) are the same as in Example 1;
[0063] (5) heating to 700°C to 750°C at a heating rate of 4°C / min to 6°C / min and 12°C / min to 15°C / min, respectively, for nucleation treatment for 0.5h to 2h;
[0064] (6) and (7) are the same as in Example 1. Thus, the number 4﹟ 1 and 4﹟ 2 of glass-ceramics. Detect 4, 4﹟ 1 and 4﹟ 2 The performance and appearance of the test results are shown in Table III.
[0065] Example 3: The example of the present application also discloses a microcrystalline glass production system, including a batching device, a melting furnace, a calendering and forming device, a crystallization annealing furnace and other components, so as to realize the continuous production of microcrystalline glass.
[0066] Specifically, as attached Figure 1 and attached Figure 2 As shown, the crystallization annealing furnace includes a roller kiln 10 , a mesh belt conveyor, a heating component and a radiation element 40 .
[0067] The roller kiln 10 is provided with a primary annealing zone, a nucleation zone, a crystallization zone and a secondary annealing zone in sequence along the feeding and discharging directions. The mesh belt 20 of the mesh belt conveyor is laid on the roller 11 of the roller kiln and moves along the feeding and discharging directions under the action of the roller 11. The heating assembly is arranged in the heating section of the roller kiln 10, which includes a first heating element 31 symmetrically arranged on the upper and lower sides of the roller 11 and horizontally equidistantly arranged along the feeding and discharging directions, and a second heating element 32 arranged on both sides of the roller kiln 10; wherein, the two ends of the first heating element 31 are connected to both sides of the roller kiln 10, and the second heating element 32 extends vertically along the kiln top of the roller kiln 10 to the bottom of the roller kiln 10. The radiation element 40 is made of silicon carbide material and is arranged in a hood shape between the roller 11 and the heating assembly to separate the roller 11 and the heating assembly.
[0068] In actual use, the second heating element 32 is used to heat both sides of the roller kiln 10 to supplement the heat dissipated outward by both sides of the roller kiln 10, thereby reducing the horizontal temperature difference in the kiln; at the same time, by setting the radiation element 40, the first heating element 31 and the second heating element 32 first heat the radiation element 40, and then the radiation element 40 heats the glass on the mesh belt 20, which is beneficial to improve the temperature uniformity in the kiln and avoid the quality of the microcrystalline glass being affected by uneven temperature during heat treatment of the glass; finally, compared with roller conveying, the mesh belt is used for transportation. The mesh belt can not only ensure the flatness of large-sized glass, but also avoid the phenomenon of broken plates, which is beneficial to improve the qualified rate of microcrystalline glass.
[0069] In this embodiment, the batching device, the melting furnace, and the calendering device all adopt the existing technology, which will not be described in detail here.
[0070] The specific implementation methods described above further illustrate the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above description is only the specific implementation method of the present application and is not intended to limit the scope of protection of the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A lithium aluminum silicon glass-ceramic, the raw materials comprising a main material, a crystal nucleating agent, a clarifier and a rare earth dopant; characterized in that: The components of the crystal nucleating agent and their mass fractions of the total weight of the raw materials include: Titanium oxide 0.5% to 1.0%; Zirconia 1.5% to 2.3%; Lithium fluoride 1.0% to 2.5%; Phosphorus pentoxide 1.5% to 2.5%; The components of the rare earth dopant and their mass fractions in the total weight of the raw materials include: Neodymium trioxide 0.01% to 0.05%; Cerium dioxide 0.05% to 0.13%; The lithium aluminum silicon series glass-ceramics is produced by a glass-ceramics production system, which comprises a batching device, a melting furnace, a rolling forming device and a crystallization annealing furnace, wherein the crystallization annealing furnace comprises: A roller kiln, wherein a primary annealing zone, a nucleation zone, a crystallization zone and a secondary annealing zone are sequentially arranged along the feeding and discharging directions; a mesh belt conveyor, wherein the mesh belt is laid on the roller of the roller kiln and moves along the feeding and discharging directions under the action of the roller; A heating assembly is arranged in the heating sections of the primary annealing zone, the nucleation zone, the crystallization zone and the secondary annealing zone; A radiation member is disposed between the heating assembly and the roller to separate the heating assembly and the roller; The mass fraction of the clarifier to the total weight of the raw materials is 0.8% to 1.2%; The clarifiers include sodium nitrate, ammonium chloride, arsenic trioxide and antimony trioxide.
2. The lithium aluminum silicon glass-ceramics according to claim 1, characterized in that: The heating assembly comprises: a first heating element, which is symmetrically arranged on the upper and lower sides of the roller and is horizontally equidistantly arranged along the feeding and discharging directions; The second heating element is located on both sides of the roller kiln and vertically extends along the kiln top of the roller kiln to the bottom of the roller kiln.
3. The lithium aluminum silicon glass-ceramics according to claim 1, characterized in that: The components of the clarifier include, by mass fraction, the following: Sodium nitrate 10% to 25%; Ammonium chloride 10% to 20%; A mixture of arsenic trioxide and antimony trioxide 60% to 80%.
4. The lithium aluminum silicon glass-ceramics according to claim 1, characterized in that: The components of the main material and their mass fractions of the total weight of the raw materials include: Silicon dioxide 68% to 73%; Lithium oxide 3.1% to 4%; Alumina 13% to 18%; Magnesium oxide 0.7% to 1.2%; Zinc oxide 0.8%~1.4%; Calcium oxide 0.4% to 0.7%; Boron oxide 0% to 0.2%; A mixture of potassium oxide and sodium oxide 1.8% to 2.1%.
5. The lithium aluminum silicon glass-ceramics according to claim 1, characterized in that: The main crystalline phase of the lithium aluminum silicon system glass-ceramics is quartz solid solution.
6. A method for preparing lithium aluminum silicon glass-ceramics according to claim 5, characterized in that: The steps include: S1. Proportioning: mixing and grinding the main material and the crystal nucleating agent, and uniformly mixing with the clarifier and the rare earth dopant to obtain a mixture; S2, melting and clarification: melting the mixed material at 1600°C to 1650°C, and then clarification treatment is performed to obtain glass liquid; S3, cooling and molding; S4, stress relief annealing: annealing the formed glass at 600℃~650℃ for 1h~2h; S5. Nucleation: Heat the annealed glass to a nucleation temperature of 700°C to 750°C at a heating rate of 8°C / min to 10°C / min. 0.5h~2h; S6, crystallization: the nucleated glass is further heated to 850°C to 900°C for crystallization treatment for 1h to 2h; S7. Cooling to obtain lithium aluminum silicon glass-ceramics.
7. The method for preparing lithium aluminum silicon glass-ceramics according to claim 6, characterized in that: In step S6, the temperature is raised to 850° C. to 900° C. at a rate of 4° C. / min to 6° C. / min.
8. The method for preparing lithium aluminum silicon glass-ceramics according to claim 6, characterized in that: In step S7, the temperature is first lowered to 500° C. to 550° C. at a rate of 15° C. / min to 20° C. / min, kept at that temperature for 0.5 h to 1 h, and then air-cooled to room temperature.
Citation Information
Patent Citations
Low-expansion-coefficient transparent microcrystalline glass and preparation method thereof
CN116332517A
Glass ceramic containing fluorine phosphorus lithium aluminium silican and its preparation method
CN1785869A